Zinc Alleviates Cadmium Induced Toxicity in Vigna radiata (L.) Wilczek - Srivastava1,; V. P. Singh1, Manoj Kumari1*, V.K. Sinhal2, Alok (Journal of Phytology, 2011)
Cadmium is a non-essential toxic element without any metabolic significance whereas Zn is an essential element but turns toxic at higher concentrations. The analysis of waste water of Bareilly city shows the presence of Cd (0.2 mgL-1) and Zn (7.3 mgL-1). Therefore, the present investigation was designed to evaluate the interactive effect of various concentrations of Zn (6.3, 7.3 and 8.3 mgL-1) with Cd (0.2 mgL-1) in Vigna radiata. Plants were treated with Cd (0.2 mgL-1) and Zn (6.3, 7.3 and 8.3 mgL-1) alone and in combination with each other. The growth parameters like plant height, fresh weight of plants, number of root nodules, chlorophyll `a` and `b` content and biochemical parameters like nitrate reductase (NR) activity, glutamine oxo glutarate aminotransferase (GOGAT) activity, and protein content were significantly reduced under the influence of Cd (0.2 mgL-1) and Zn (6.3, 7.3 and 8.3 mg L-1) as compared to their respective controls while glutamate dehydrogenase activity was increased under these conditions. However, growth and biochemical parameters were increased with combined treatment of Zn and Cd as compaired to Cd treatment alone while GDH activity was decreased under these conditions. The Zn treatment did not show significant reduction at lower concentration but at higher concentration (8.3 mgL-1) inhibitory effect on groth parameters were observed. The variety K-851 was found to be more susceptible to metal induced toxicity than variety PDM-139.